Marine-inspired molecular mimicry generates a drug-free, but immunogenic hydrogel adhesive protecting surgical anastomosis - Jinjian Huang; Yungang Jiang; Ye Liu; Yanhan Ren; Ziyan Xu; Zongan Li; Yun Zhao; Xiuwen Wu; Jianan Ren (Bioactive Materials, 2021)
Herein, we report the synthesis of a biomimic hydrogel adhesive that addresses the poor healing of surgical anastomosis. Dopamine-conjugated xanthan gum (Da-g-Xan) is fabricated using deep insights into the molecular similarity between mussels' adhesive and dopamine as well as the structural similarity between barnacle cement proteins and xanthan gum. The hydrogel mimics marine animals’ adherence to wet tissue surfaces. Upon applying this adhesive to colonic anastomosis in a rat model, protective effects were shown by significantly improving the bursting pressure. Mechanistically, the architecture of Da-g-Xan hydrogel is maintained by dynamic intermolecular hydrogen bonds that allow the quick release of Da-g-Xan. The free Da-g-Xan can regulate the inflammatory status and induce type 2 macrophage polarization (M2) by specifically interacting with mannose receptors (CD206) revealed by RNA-sequencing and molecular binding assays. Consequently, an appropriate microenvironment for tissue healing is created by the secretion of chemokines and growth factors from M2 macrophages, strengthening the fibroblast migration and proliferation, collagen synthesis and epithelial vascularization. Overall, this study demonstrates an unprecedented strategy for generating an adhesive by synergistic mimicry inspired by two marine animals, and the results show that the Da-g-Xan adhesive augments native tissue regenerative responses, thus enabling enhanced recovery following surgical anastomosis.